Comparative evaluation of spoilage-related bacterial diversity and metabolite profiles in chilled beef stored under air and vacuum packaging. (February 2019) - Mansur, Ahmad Rois; Song, Eun-Ji; Cho, Yong-Sun; Nam, Young-Do; Choi, Yun-Sang; Kim, Dae-Ok; Seo, Dong-Ho; Nam, Tae Gyu
Abstract: Microbial spoilage is a complex event to which different bacterial populations and metabolites can contribute depending on the storage conditions. This study explored the evolution of spoilage and related volatile organic compounds (VOCs) in chilled beef under air and vacuum packaging (VP). The results suggested that different storage conditions affected changes in bacterial communities and metabolites in beef and consequently affected the odor properties of the stored beef, thereby leading to spoilage. Bacterial species belonging to Pseudomonadaceae ( Pseudomonas spp.) and lactic acid bacteria ( Lactobacillus sp.) dominated the bacterial communities in beef stored under air and VP, respectively, with several VOCs associated with off-odors of the stored beef and most likely produced by both bacteria. Our results suggested several microbial VOCs that could be used as potential spoilage indicators, including acetic acid, butanoic acid, and 2-butanone in VP-stored beef and 3-methylbutan-1-ol, ethyl acetate, acetoin, 2-butanone, and diacetyl in air-stored beef. These findings might provide valuable information regarding the quality monitoring of beef during storage. Highlights: Air storage and vacuum packaging differentially affect beef microbial dynamics. Storage modality alters volatile organic compound (VOC) production in stored beef. Bacterial VOCs correlated with off-odor might be useful for beef quality monitoring.